PENYULUHAN PEMBERDAYAAN MASYARAKAT BERBASIS DIGITAL UNTUK DESA WISATA - Adha, Howardi Visza; Astari, Silvy; Suhanda, Mya Yuwanita (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
Community service is organized by lecturers at the Faculty of Economics and Business, Baiturrahmah University. The aim of this activity is to provide digital-based community empowerment outreach for tourism villages in Nagari Koto Nan Duo, Batang Kapas District, Pesisir Selatan Regency, on August 10 2024, West Sumatra Province. Villages are the smallest government units that play an important role in sustainable development through village autonomy, as mandated in Law Number 6 of 2014 concerning Villages. With increasing digital penetration in Indonesia, including in rural areas, digital-based community empowerment has become relevant and potential. This empowerment includes building information technology infrastructure, increasing digital literacy, developing the creative economy, and digital marketing. Previous research has shown the success of digital-based empowerment programs in various villages, such as creative economy development, digital tourism, and website-based public services. This article aims to describe digital-based village community empowerment practices, providing guidance for policy makers, facilitators and academics in optimizing the potential of technology to improve the welfare of village communities. It is hoped that this program can be a sustainable solution to support rural development in the digital era. Keywords: Extension, Digital Based, Tourism Village.